The Profile of Students' Science Process Skills on Heat and Its Transfer Content Using an Ethnoscience Approach (Uha Food Making in Liang Village, Central Maluku) - Tamaela, Elsina Sarah; Kereh, Cicylia T.; Latupeirissa, Asry N.; Manuhuttu, Ledy; Sahetapy, Mariana S. (KnE Social Sciences, 2024)
Physics learning can be carried out by involving cultural elements in it. One approach that can be used is ethnoscience—an integrated physics learning with the culture of making the typical food of the Liang Village Community in Central Maluku Regency, namely Uha. The production process of Uha can be used to teach the concept of heat and its transfer and also to train science process skills to students. This research involved 23 students who were residents of Liang Village. The instrument for data collection was a set of 13 science process skills test questions. Students’ worksheets were analyzed descriptively. Based on the analysis results, each process skill indicator were found to be poor. Thus, it can be concluded that the students’ science process skills still need to be trained in an integrated manner in physics learning activities in the classroom. Keywords: science process skills, ethnoscience